Preservation Effect of Nisin and Chitosan on the Quality of Patin (Pangasius hypophthalmus) Fillets During Cold Storage - Rohula Utami; Ulfianiza Rachmah; Ardhea Mustika Sari (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2026)
Patin is a type of fish commonly processed into fillets for export purposes. Patin fillets are prone to deterioration during cold storage. Nisin is a natural preservative that inhibits microbial growth, particularly Gram-positive bacteria; however, it remains ineffective against Gram-negative bacteria. A combination of nisin and chitosan has been reported to inhibit Gram-negative bacteria. This study aimed to analyze the effect of combining nisin from Lactococcus lactis subsp. lactis and chitosan, applied by bottle-spraying, on the quality parameters (total plate count/TPC, pH, total volatile base nitrogen/TVB-N, and thiobarbituric acid/TBA) of patin fillets during cold storage (4±1 °C) for 16 days. The treatments consisted of 2% chitosan, combinations of nisin–chitosan (125 IU ml-1 nisin and 1.5% chitosan, 250 IU ml-1 nisin and 1% chitosan, 500 IU ml-1 nisin and 0.5% chitosan), and 1,000 IU ml-1 nisin. The results showed that both the combined treatments of nisin and chitosan, as well as the individual applications of 1,000 IU ml-1 nisin and 2% chitosan, slowed the increase in TVB-N and TBA values. However, these treatments did not significantly affect pH or microbiological quality (TPC). The combination treatment effectively delayed chemical spoilage (TVB-N, TBA) during cold storage; however, microbial limits (TPC) were reached by day 12, indicating that the overall shelf life of patin fillets could not be extended beyond this period.